Touch and Go: Membrane Contact Sites Between Lipid Droplets and Other Organelles - Liao, Pin-Chao; Yang, Emily J.; Borgman, Taylor; Boldogh, Istvan R.; Sing, Cierra N.; Swayne, Theresa C.; Pon, Liza A. (Frontiers in Cell and Developmental Biology, 2022)
Lipid droplets (LDs) have emerged not just as storage sites for lipids but as central regulators of metabolism and organelle quality control. These critical functions are achieved, in part, at membrane contact sites (MCS) between LDs and other organelles. MCS are sites of transfer of cellular constituents to or from LDs for energy mobilization in response to nutrient limitations, as well as LD biogenesis, expansion and autophagy. Here, we describe recent findings on the mechanisms underlying the formation and function of MCS between LDs and mitochondria, ER and lysosomes/vacuoles and the role of the cytoskeleton in promoting LDs MCS through its function in LD movement and distribution in response to environmental cues.